System of Quality Control of Design and Construction Activities in the Republic of Uzbekistan - A., Suyunov; R., Murodov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article describes the stages of creating a quality control system for design and construction activities in the Republic of Uzbekistan based on a market mechanism. There are also issues of implementation of the state control system for design and construction activities based on the requirements of ISO-9001.